The Myth of the Metropolis: The Role of the City in Canadian Regionalism - McCann, L. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
The concept of metropolitanism, long an accepted fact in Canadian life and letters, has assumed the status of a national myth. Canada is no longer a country structured simply as metropolis and hinterland. Resource wealth has fostered sustained hinterland development and created regional metropolitan centres which directly influence the nation's economic, social, and political life. The strength of regional cities today affects both the redirection of national life and the renewed expression of regionalism which currently characterizes Canada.